Auditory perceptual performance of children in the identification of contrasts between stressed vowels - Berti, Larissa Cristina [UNESP]; Roque, Lívia Mayra Rodrigues [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2013)
Purpose: To assess the auditory perceptual performance of children in a task of identification of vowel contrasts, to classify which phonemes and vowel contrasts provide higher or lower degrees of difficulty, and to verify the influence of age in this performance. Methods: Data recordings of auditory perceptual performance of 66 children in a task of identification using the software Perception Evaluation Auditive & Visuelle (PERCEVAL) were selected from a database. The task consisted of presenting sound stimuli through headphones to children, who would then choose, from two pictures arranged on the computer screen, the one corresponding to the word they heard. The time between auditory inputs and the child's reaction was automatically computed in the software. Results: The perceptual accuracy was 88% and we found a positive correlation with the variable age. The time of response was significantly longer for incorrect answers as opposed to correct answers (p=0.00). Different degrees of similarity in auditory perception were observed, where front vowels were similar more often than back vowels. The tendency for errors was prevalent in the range of non-peripheral to peripheral vowels, which suggests that the latter may serve as a reference or perceptual anchor. Conclusion: The auditory perceptual ability concerning the identification of vowel contrasts is not yet established in the age group studied. The auditory perception of vowel contrasts occurs gradually and asymmetrically, as the order of acquisition in terms of production and perception was not always the same.

OBJETIVOS: Investigar o desempenho perceptivo-auditivo de crianças no tocante à identificação de contrastes entre as vogais tônicas; identificar quais fonemas e contrastes vocálicos indicam maior ou menor grau de dificuldade de identificação; e verificar se a idade influencia a acurácia perceptivo-auditiva. MÉTODOS: Foram selecionadas, de um banco de dados, informações referentes ao desempenho perceptivo-auditivo de 66 crianças em uma tarefa de identificação perceptivo-auditiva da classe das vogais tônicas do Português Brasileiro. Com o uso do software Perception Evaluation Auditive & Visuelle (PERCEVAL), foram apresentados os estímulos acústico e visual solicitando da criança a escolha da gravura correspondente à palavra apresentada auditivamente dentre duas possibilidades de imagens dispostas na tela do computador. O tempo de apresentação do estímulo e de reação das crianças foi computado automaticamente pelo software. RESULTADOS: Observou-se acurácia perceptivo-auditiva de 88% das crianças e correlação positiva com a idade. A variância do tempo de reação dos erros foi superior à dos acertos (p=0,00). Foram observados diferentes graus de similaridade perceptivo-auditiva: vogais anteriores registraram maior similaridade do que vogais posteriores. A tendência que prevaleceu nos erros foi a das vogais menos para as mais periféricas, sugerindo que estas últimas parecem servir como pontos de ancoragem na percepção. CONCLUSÃO: A habilidade perceptivo-auditiva no tocante à identificação de contrastes vocálicos ainda não está estabilizada na faixa etária estudada. O domínio perceptivo-auditivo dos contrastes vocálicos se dá de forma gradativa e assimétrica, e o paralelismo entre a ordem de aquisição em termos de produção e em termos de percepção nem sempre se manteve.
Desempenho perceptivo-auditivo de crianças na identificação de contrastes fonológicos entre as vogais tônicas
Keywords: Auditory perception; Evaluation; Speech; Phonetics; Child; Percepção auditiva; Avaliação; Fala; Fonética; Criança